Niche breadth and geographic range size as determinants of species survival on geological time scales. Issue 10 (2nd June 2015) - Saupe, Erin E.; Qiao, Huijie; Hendricks, Jonathan R.; Portell, Roger W.; Hunter, Stephen J.; Soberón, Jorge; Lieberman, Bruce S.
Abstract Aim Determining which species are more prone to extinction is vital for conserving Earth's biodiversity and for providing insight into macroevolutionary processes. This paper utilizes the Pliocene to Recent fossil record of mollusks to identify determinants of species' extinction over the past three million years of Earth history. Location Western Atlantic. Methods We focus on 92 bivalve and gastropod species that lived during the mid‐Pliocene Warm Period (mPWP; ∼3.264–3.025 Ma) and have either since gone extinct or are still extant. We used ecological niche modeling (ENM) to assess the vulnerability of these species to extinction as a function of both fundamental (FN) and realized (RN) niche breadth proxies, geographic range size, and amount of suitable area available to them during the Last Glacial Maximum (LGM; ∼21 Ka). Results Geographic range size emerged as a key predictor of extinction for the studied mollusk species, with RN breadth and amount of suitable area available during the LGM as secondary predictors. By contrast, FN breadth was not a significant predictor of extinction risk. Main conclusions The failure to recover FN breadth as a predictor of extinction may suggest that extinction resistance is achieved when species are more successful in filling the geographic extent of their fundamental tolerances. That is, when it comes to species' survival, being a generalist or specialist sensu stricto may be secondary to the unique historical, dispersal, and biotic constraints that dictate a species' occupation of suitable environments, and consequently of geographic space, at a particular time. Identifying the factors that promote extinction is important because of the time‐intensive nature of estimating extinction risk for individual species and populations, and because of the rising concerns about the future of marine ecosystems and biodiversity.